2015
DOI: 10.1186/s12863-015-0250-8
|View full text |Cite
|
Sign up to set email alerts
|

Development of SSR markers and genetic diversity analysis in enset (Ensete ventricosum (Welw.) Cheesman), an orphan food security crop from Southern Ethiopia

Abstract: BackgroundEnset (Ensete ventricosum (Welw.) Cheesman; Musaceae) is a multipurpose drought-tolerant food security crop with high conservation and improvement concern in Ethiopia, where it supplements the human calorie requirements of around 20 million people. The crop also has an enormous potential in other regions of Sub-Saharan Africa, where it is known only as a wild plant. Despite its potential, genetic and genomic studies supporting breeding programs and conservation efforts are very limited. Molecular met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
59
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(77 citation statements)
references
References 50 publications
16
59
2
Order By: Relevance
“…The results presented here indicate that cultivated and wild enset accessions exhibit similar gene diversity and polymorphic information content (PIC) (Table 4). This is similar to what has been reported based on SSR marker analysis of enset genetic diversity (Gerura et al , 2019), but differs from what has been reported by Olango et al (2015), which reported that higher gene diversity in cultivated enset population (0.59) than wild enset population (0.40), but similar hetrozygosity for cultivated and wild enset populatons (0.5). The genetic diversity for both cultivated and wild enset reported in the current study (Table 4) is lower than previous enset genetic diversity studies conducted using SSR makers (Getachew et al , 2014; Olango et al, 2015 ; Gerura et al , 2019).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The results presented here indicate that cultivated and wild enset accessions exhibit similar gene diversity and polymorphic information content (PIC) (Table 4). This is similar to what has been reported based on SSR marker analysis of enset genetic diversity (Gerura et al , 2019), but differs from what has been reported by Olango et al (2015), which reported that higher gene diversity in cultivated enset population (0.59) than wild enset population (0.40), but similar hetrozygosity for cultivated and wild enset populatons (0.5). The genetic diversity for both cultivated and wild enset reported in the current study (Table 4) is lower than previous enset genetic diversity studies conducted using SSR makers (Getachew et al , 2014; Olango et al, 2015 ; Gerura et al , 2019).…”
Section: Discussionsupporting
confidence: 84%
“…The high heterozygosity of cultivated enset might be due to vegetative propagation maintaining heterozygosity across clonal generations. In addition, the wild enset habitat has been sharply declining in Ethiopia because of population growth and deforestation (Birmeta et al, 2004; Olango et al, 2015). This reduction in effective population size might have contributed to the observed lower heterozygosity due to the increase of chances of inbreeding in wild enset populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cheesm.) (Olango et al 2015); tef (Eragrostis tef (Zucc.)) Trotter (Bedane et al 2015;Ayalew et al 2015); coffee (Tadele et al 2014); sesame (Gebremichael and Parzies 2011); and barley (Muhe and Assefa 2011) have many landraces shown to have high genetic diversity in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%